1999
DOI: 10.1038/sj.bmt.1702066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CD34+ cell dose in long-term engraftment following autologous peripheral blood stem cell transplantation

Abstract: Summary:The number of CD34 ؉ cells has been described as the best parameter for predicting the quality of engraftment in peripheral blood progenitor cell (PBPC) transplantation in the early post-transplant period. In this study we have determined the optimal number of CD34 ؉ cells in order to maintain engraftment in the long term in a series of 100 patients receiving autologous PBPC transplantation. Based on our previous experience on the speed of early hematopoietic recovery, four subgroups of patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 20 publications
3
54
1
1
Order By: Relevance
“…In our study, in accordance with previous reports, [8][9][10]31 we found that the CD34 þ cell dose infused directly influenced the speed of neutrophil and platelet engraftment. In addition, it was the single factor affecting long-term engraftment.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, in accordance with previous reports, [8][9][10]31 we found that the CD34 þ cell dose infused directly influenced the speed of neutrophil and platelet engraftment. In addition, it was the single factor affecting long-term engraftment.…”
Section: Discussionsupporting
confidence: 82%
“…It should be pointed out that we have used a very sensitive and specific method in which 300 000 events were screened. The reproducibility of this method, and its ability to predict the speed of hematopoietic recovery, 8,9 indicates that this is a reliable method for the assessment of progenitor-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown a reduction in RBC transfusion requirements with higher stem cell doses, 20,21 we did not find this to be the case in our patient population. The lack of an association between stem cell dose and RBC transfusions may be due to a relatively higher incidence of grades 3-4 hemorrhagic complications in our study group (13.8%).…”
Section: Discussioncontrasting
confidence: 45%
“…The rapid recovery of neutrophils and plts after AHSCT has been extensively studied and many reports have associated this with the total number of CD34 þ hemopoietic progenitor cells present in the infused autograft. [17][18][19]33 All our patients met the minimum recommended stem cell dose of 2.5 Â 10 6 CD34/kg, and this likely explains the early neutrophil and plt engraftment observed.…”
Section: Discussionmentioning
confidence: 99%